2019
DOI: 10.1111/sum.12496
|View full text |Cite
|
Sign up to set email alerts
|

Off‐site impacts of soil erosion and runoff: Why connectivity is more important than erosion rates

Abstract: Off-site impacts of soil erosion are of greater social and economic concern in Western Europe than on-site impacts. They fall into two related categories: muddy flooding of properties and ecological impacts on watercourses because of excessive sedimentation and associated pollutants. Critical to these impacts is the connectedness of the runoff and sediment system between agricultural fields and the river system. We argue that well-connected systems causing off-site damage are not necessarily related to areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 47 publications
0
75
0
Order By: Relevance
“…Human interference with the water cycle occurs at multiple spatiotemporal scales around the globe (Falkenmark et al, ), affecting nearly every water store and flux, yet this is often under‐represented in our understanding and depiction of water cycles (Abbott et al, ). Here, we have shown that artificial drainage and other land management practices that increase the connectivity of surface and subsurface waters to the streams (Boardman, Vandaele, Evans, & Foster, ; Shuster, Bonta, Thurston, Warnemuende, & Smith, ) can have a profound effect on the evolution of water ages. The extensive short‐circuiting of hydrological pathways that we found in the catchment can radically change storage–flux interactions, diminishing a natural catchment buffering capacity, especially under extreme conditions (Remondi et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…Human interference with the water cycle occurs at multiple spatiotemporal scales around the globe (Falkenmark et al, ), affecting nearly every water store and flux, yet this is often under‐represented in our understanding and depiction of water cycles (Abbott et al, ). Here, we have shown that artificial drainage and other land management practices that increase the connectivity of surface and subsurface waters to the streams (Boardman, Vandaele, Evans, & Foster, ; Shuster, Bonta, Thurston, Warnemuende, & Smith, ) can have a profound effect on the evolution of water ages. The extensive short‐circuiting of hydrological pathways that we found in the catchment can radically change storage–flux interactions, diminishing a natural catchment buffering capacity, especially under extreme conditions (Remondi et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…Using our understanding of particle size dependent connectivity for managing sediment delivery opens up new opportunities to explore different strategies. A detailed discussion regarding management strategies is beyond the scope of the present paper but a range of strategies for the River Rother have recently been explored by Boardman et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Such conceptualisations can often be used to justify sampling frameworks for sediment‐associated contaminant assessment (e.g., Mokwe‐Ozonzeadi, Foster, Valsemi‐Jones, & McEldowney, ) or management interventions, which either improve or reduce both structural and/or functional connectivity (e.g. Boardman, Vandaele, Evans, & Foster, ). The conceptual model in Figure illustrates those factors that could boost or form barriers to sediment transfer at the catchment/landscape scale and identify natural and anthropogenic factors that might exist in a typical lowland UK catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Increased leaching, drain-flow, and surface run-off have been identified as the major pathways leading to ecological exposure to contaminants (Boardman et al 2019;Sandin et al 2018;Tsaboula et al 2019). The extent of how these processes contribute to the ecological exposure depends on the soil properties, the physico-chemical characteristics of the substances and on the formulation (Gouy et al 1999;Sandin et al 2018).…”
Section: Bioassays Assessment: Dry Vs Rainy Seasonmentioning
confidence: 99%